The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/chemengineering3030062
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Ultrasonic Synthesis and Magnetic-Field-Assisted Arrangement of Nanosized Crystallites of Cobalt-Containing Layered Double Hydroxides

Abstract: High-quality stoichiometric Co2Al–NO3 and Co2Al–CO3 layered double hydroxides (LDHs) have been obtained by precipitation followed by anion exchange, both high-power-sonication assisted. Application of high-power ultrasound has been demonstrated to result in a considerable acceleration of the crystallization process and the anion-exchange reaction. Two independent approaches were used to form bulk and 2-D samples of Co2Al–NO3 with the oriented crystallites, namely uniaxial pressing of deposits from sonicated LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The red arrows represent magnetic moments of Co II cations. The presence of the directional magnetic anisotropy due to g-factor anisotropy gzz>>gxx,gyy confirms by SEM images (cross section views) of layers of the Co(2)Al-NO3 crystallites deposited on glass substrates without (b) and with (c) application of magnetic field[12]. Magnetic field was applied perpendicular to the substrate surface.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The red arrows represent magnetic moments of Co II cations. The presence of the directional magnetic anisotropy due to g-factor anisotropy gzz>>gxx,gyy confirms by SEM images (cross section views) of layers of the Co(2)Al-NO3 crystallites deposited on glass substrates without (b) and with (c) application of magnetic field[12]. Magnetic field was applied perpendicular to the substrate surface.…”
supporting
confidence: 57%
“…Directional magnetic anisotropy that suggests a respective short range order in Co(2)Al-NO3 is uncovered under application of static magnetic field during precipitation of dispersed flake-like nanocrystallites of this LDH [12]. It has been shown that the aligning action of magnetic field results in highly oriented dense layers of the Co(2)Al-NO3 nanocrystallites with the flake surfaces perpendicular to the magnetic field (Fig.…”
Section: Experimental Details and Sample Preparationmentioning
confidence: 92%
See 1 more Smart Citation
“…28 Magnesium layered hydroxide (MgLH) is a non-toxic material that has a wide range of applications such as in cosmetic products, serving as a catalyst in flame-retardants and has been used as inorganic absorbents, etc. [29][30][31] MgLH has a layered structure in which the hydroxide ions surround the magnesium ion in an octahedral manner. 30 Infinite layers are formed by these octahedral units by edge-sharing with hydroxide ions in the planes of the layers.…”
Section: Introductionmentioning
confidence: 99%